IMPLEMENTASI PERATURAN MENTERI KOMUNIKASI DAN INFORMATIKA NOMOR 19 TAHUN 2014 DALAM PENANGANAN SITUS INTERNET BERMUATAN NEGATIF (Studi Kasus Pemblokiran terhadap Situs Radikal oleh Kemenkominfo Tahun 2015) - Musyafak, Najahan; Handayani, Maya Rini; ., Kumarudin (Islamic Communication Journal, 2017)
At the end of March 2015 the Ministry of Communications and Informatics (Kemenkominfo) blocking 22 internet sites that are considered radically charged or sympathizers of Â radicalism. Kemenkominfo serves to keep sites Â that Â campaignradicalism can be minimized. This authority is contained in the